Containing COVID-19: Implementation of Early and Moderately Stringent Social Distancing Measures Can Prevent The Need for Large-Scale Lockdowns. Issue 1 (29th July 2020) - Koh, Wee Chian; Alikhan, Mohammad Fathi; Koh, David; Wong, Justin
Guidance from many health authorities recommend that social distancing measures should be implemented in an epidemic when community transmission has already occurred. The clinical and epidemiological characteristics of COVID-19 suggest this is too late. Based on international comparisons of the timing and scale of the implementation of social distancing measures, we find that countries that imposed early stringent measures recorded far fewer cases than those that did not. Yet, such measures need not be extreme. We highlight the examples of Hong Kong and Brunei to demonstrate the early use of moderate social distancing measures as a practical containment strategy. We propose that such measures be a key part of responding to potential future waves of the epidemic.